The contribution of the environment and genes to the development of personality in three-spined stickleback (Gasterosteus aculeatus) & Aggression and attraction: aggressive three-spined stickleback (Gasterosteus aculeatus) males show increased sexual signalling effort - Reddish, Amelia (2017)
Personality, once a term restricted exclusively to Homo sapiens, is now a widespread subject in the field of behavioural ecology. A major area of debate for personality researchers is one which questions the relative contributions of environment and genes on personality, mirroring the “nature versus nurture” debate in human personality studies. Another major question considers the development of personality and its stability over ontogeny. This study aimed to investigate the role of genes and the environment on the development of personality and behavioural syndromes. Wild stickleback from five geographically separated lochs on North Uist, Scotland, were analysed for boldness, activity and exploration. Offspring of these wild fish were laboratory reared in standardised conditions and assayed in their juvenile and adult stage to investigate personality change across development. The only differences between the populations of lab-reared fish was the loch their parents originated from. Results indicated clear behavioural differences between adult wild and adult lab-reared populations despite similar genotypes. Adult lab-reared fish exhibited lower levels of activity, exploration and boldness than wild fish. There were no significant differences in behaviour between the populations of adult lab-reared stickleback. However, wild fish and juvenile lab-reared fish showed significant behavioural variation between populations. These results tentatively point towards a leading role of the environment in shaping behaviour. However, behaviour was not stable across development. Juvenile behaviour showed some similarities to wild adult behaviour, but these similarities were lost over maturation. These results suggest that initial gene effects may be compounded by experience/environmental influences. Personality may be subject to developmental plasticity allowing for individuals with similar genotypes to show differing behavioural phenotypes. Personality imposes a limitation on behavioural plasticity resulting in trade-offs dependent on personality type. For example, aggressive males may put more effort into reproduction at a cost to survival (Smith and Blumstein, 2008). Recently, researchers have begun to look into how personality interacts with aspects of life history. One approach is to look at how personality traits correlate with traits influencing aspects of life history such as sexual signalling. This study aims to investigate whether personality traits boldness, and aggression, correlate with behavioural and ornamental sexual signals in the three-spined stickleback (Gasterosteus aculeatus). In this study, male stickleback in breeding condition from a single population exhibited consistent individual variation in boldness, aggression and sexual signals. All sexual signals measured (colouration, nest building and courtship behaviours) correlated with each other to form a “reproductive syndrome”. Aggression correlated positively with all sexual signals and signalling quality appeared to increase with aggression levels. It is hypothesised that this is likely due to aggressive males putting more effort into signalling/reproductive behaviour with a trade-off of reduced survival. Furthermore, aggression and signalling effort were significantly greater in males that built nests during the experimental period. Finally, males appeared to modulate their signalling effort based on the presence of competitive rivals. Males held in single sex tanks prior to the experimental trials expressed higher levels of aggression and sexual signalling behaviours than males in mixed sex tanks. Whilst some research has investigated the role of personality in mate choice, little research has explored the relationship between signal quality and personality. The results of this study demonstrate that personality and sexual signalling are intricately linked. Further research incorporating a wider grouping of personality traits is needed to better understand the trade-offs between personality type and sexual signalling.